Association between ABCB4 variants and intrahepatic cholestasis of pregnancy - Dekun Zhang; Yuhong Li; Shufeng He; Jing Shu; Tiechen Li; Qing Sun (Scientific Reports)
Abstract The ABCB4 gene encodes multidrug resistance protein 3(MDR3), which is a phosphatidylcholine(PC) transfer enzyme that transfers lecithin from the inner part of the phospholipid bilayer to the extracellular bile. The occurrence of intrahepatic cholestasis of pregnancy(ICP) is closely related to ABCB4 variants, but there is limited research on this topic in southern Anhui, China. We sequenced ABCB4 in pregnant women with ICP and healthy pregnant women to explore the relationship. A total of 30 patients diagnosed with ICP were selected as the study objects and 90 healthy pregnant women were selected as the control group. DNA was extracted from peripheral blood of ICP patients and healthy pregnant women, 27 exons were sequencing by Sanger sequencing. Polymerase chain reaction (PCR) was used to amplify those exons. PolyPhen2, Mutation Taster, Provean, SIFT and Mutpred2 were used to predict protein structure, and Pymol software was used to predict the impact of missense variant c.1954 A > G(p.Arg652Gly) on proteins. Four exonic variants of ABCB4 gene were detected in ICP patients and healthy pregnant women, including synonymous variants c.175 C > T, c.504 C > T,c.711 A > T and missense variant c.1954 A > G(p.Arg652Gly). The incidence of the missense variant c.1954 A > G(p.Arg652Gly) was 6/90 in healthy pregnant womenand 8/30 in ICP patients.In healthy pregnant women with the missense variant c.1954 A > G(p.Arg652Gly), no other exonic variants were found. In ICP patients with missense variant c.1954 A > G(p.Arg652Gly), other exonic variants were found. PolyPhen2, Mutation Taster, Provean, SIFT and Mutpred2 were used to predict that the four exonic variants were benign, while Pymol was used to showed that the missense variant was located in the linker region of MDR3 and had a slight impact on protein function. Among ICP patients with missense variant c.1954 A > G(p.Arg652Gly), patients with three exonic variants(c.504 C > T, c.711 A > T, c.1954 A > G) had higher γ-GT, TBA, ALT and AST than those with two exonic variants. ABCB4 missense variant c.1954 A > G(p.Arg652Gly) requires the combination of other variants(c.175 C > T, c.504 C > T,c.711 A > T) to cause ICP symptoms, and when combined with other variants, it has a superimposed effect.